2004
DOI: 10.1016/s0197-4580(03)00127-1
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydia pneumoniae induces Alzheimer-like amyloid plaques in brains of BALB/c mice

Abstract: Amyloid deposits resembling plaques found in Alzheimer's disease (AD) brains were formed in the brains of non-transgenic BALB/c mice following intranasal infection with Chlamydia pneumoniae. The mice were infected at 3 months of age with C. pneumoniae isolated from an AD brain. Infection was confirmed by light and electron microscopy in olfactory tissues of the mice. C. pneumoniae was still evident in these tissues 3 months after the initial infection indicating that a persistent infection had been established… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
200
3
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(213 citation statements)
references
References 44 publications
8
200
3
2
Order By: Relevance
“…These observations are in line with the present findings showing that A␤ formation may be induced in vitro following exposure of mammalian cells to B. burgdorferi. Recently, the formation of amyloid deposits resembling AD plaques was induced in the brains of mice following intranasal infection with another bacterium, Chlamydia pneumoniae [17].…”
Section: Discussionmentioning
confidence: 99%
“…These observations are in line with the present findings showing that A␤ formation may be induced in vitro following exposure of mammalian cells to B. burgdorferi. Recently, the formation of amyloid deposits resembling AD plaques was induced in the brains of mice following intranasal infection with another bacterium, Chlamydia pneumoniae [17].…”
Section: Discussionmentioning
confidence: 99%
“…Infection was confirmed by light and electron microscopy in olfactory tissues of the mice. C. pneumoniae was still evident in these tissues 3 months after the initial infection indicating that a persistent infection had been established [41].…”
Section: Alzheimer's Diseasementioning
confidence: 96%
“…The results of Balin study demonstrated the frequent infection of microglia and astroglia with C. pneumoniae in the AD-affected brain [7]. Intriguingly, an animal model, in which low-dose infusion of LPS has been used, revealed remarkable parallels with AD inflammation including APP induction, increased cytokine production with microglial reactivity, and temporal lobe pathology [41].…”
Section: Alzheimer's Diseasementioning
confidence: 97%
See 1 more Smart Citation
“…These features, including betaamyloid deposition, tau phosphorylation 35 59,75 , entorhinal and hippocampal cell loss and cerebral shrinkage 4 can all be induced by Herpes simplex viral infection in mice. Several hundred genes have been implicated in the disease 8 (see http://www.polygenicpathways.co.uk/alzpolys.html , and a number of environmental risk factors including viral infection (Herpes viruses HSV-1 36,37 and the cytomegalovirus) , and bacterial and parasitic infection (C.Pneumoniae 17,49 , Borrelia Burgdorferri 53 and Helicobacter pylori) have also been shown to promote risk 31 . Indeed eradication of H.Pylori has been reported to improve cognitive performance 44 .…”
Section: Introductionmentioning
confidence: 99%